Evaluation of the Effectiveness of CO₂ Nanobubbles as an Enhanced Oil Recovery Method on Low Permeability Artificial Core - Softy Putri Adsura; Edy Sunardi (Journal of Business, Social and Technology, 2026)
Background: Low-permeability reservoirs, characterized by limited pore connectivity and dominance of capillary forces, present significant challenges to conventional Enhanced Oil Recovery (EOR) methods. Water flooding often fails to mobilize residual oil in such reservoirs, which typically results in low recovery factors. Objective: This study aims to evaluate the effectiveness of the Enhanced Oil Recovery (EOR) method based on CO₂ nanobubbles in low-permeability artificial cores with matrix-supported characteristics. Methods: Experimental analysis was conducted on artificial cores fabricated from 80% quartz sand and 20% Portland cement. The study involved petrophysical characterization, oil saturation, and core flooding experiments using both water flooding and CO₂ nanobubble injection. Scanning Electron Microscopy (SEM) was used to observe microstructural changes and fluid redistribution. Results: The initial characterization of the artificial core showed a porosity of ±31% and permeability of approximately 5 mD. Water flooding did not increase the recovery factor (RF = 0%), while CO₂ nanobubble injection achieved a recovery factor increase of ±3.76%. SEM observations revealed more uniform fluid redistribution and reduced residual oil after nanobubble flooding, confirming the effectiveness of CO₂ nanobubbles in mobilizing oil from tight pore systems. Conclusion: The study concludes that CO₂ nanobubble-based EOR is effective in low-permeability reservoirs, with scale compatibility between nanobubble size and pore throat geometry playing a crucial role in enhancing recovery. This approach offers a promising direction for optimizing EOR in tight reservoirs.